Granulator Performance for Urea Granule Quality: A Study on Material Balance and Recycle Seed Ratio - Hidayat, Jefri Pandu; Kusuma, Muhammad Azi; Putri, Nita Ariestiana; Hariyadi, Asful (Institut Teknologi Sepuluh Nopember, 2025)
Granulation is a critical process in quality of urea fertilizer, particularly their size distribution, significantly affects the product's performance and marketability. Urea synthesis begins with the reaction between ammonia and carbon dioxide, where ammonium carbamate is decomposed to produce urea by granulation process. This research aims evaluate the performance of granulator on urea granule size product quality based on material balance and recycle seed ratio (RSR). The granulator performance in the urea granulation process was evaluated for a production capacity of 3,500 tons/day. The methodology involves data collection from operational records in six days respectively, followed by mass balance analysis and product quality evaluation based on particle size distribution. The analysis revealed a significant deviation between design and actual data. Specifically, the design mass balance indicated a total inlet of 236,726 kg/h and a total outlet of 230,575 kg/h, resulting in a mass deficit of 6,151 kg/h attributed to dust formation and water evaporation. The measured on-size product yield was approximately 98.50% at the outlet, with the desired particle size range of 2–4.75 mm. These findings provide critical insights for process optimization and resource management in urea granulation, emphasizing the need for precise operational control to minimize material losses and ensure product quality compliance with specifications.